Exergy analysis of a spray dryer: Methods and interpretations. Issue 5 (4th April 2018) - Johnson, Perry William; Langrish, Timothy Alan Granville
ABSTRACT: Exergy analysis has been used to assess the intrinsic exergy efficiency of a spray drying system modeled to produce 1.25 kg s −1 of skim milk powder. From an exergy perspective, the dryer has a low exergy efficiency of 38% (on an evaporation basis), while the efficiencies associated with the mass transfer and heat transfer are 94% (thermomechanical efficiency) and 30% (transiting exergy efficiency), respectively. The improvement potential of 575 kW, of the 722 kW energy flow in the feed, also shows that the exergy efficiencies of spray dryers are intrinsically small. Reviewing exergy efficiency factors, there appears to be no universal efficiency factor for an exergy analysis. The inevitable (INE) exergy loss method is a potential shortcut technique based on the Carnot efficiency and first law analysis. There are some limitations on using the INE method for processes that are not exclusively thermal; in those cases, an entropy balance (second law property) is more appropriate. The INE method still shows potential as a starting basis of comparison because it shows the scale and the efficiency together, which is important for targeting areas for process improvement without doing a full exergy analysis. This work is a short review of the work on dryer exergy efficiency, mainly focusing on the various factors which are used, followed by a discussion and case study testing each factor to find a potential optimization method and a discussion on each factors merits.